Associations of Hypothyroxinemia With Risk of Preeclampsia–Eclampsia and Gestational Hypertension - Su, Xiujuan; Liu, Yang; Li, Guohua; Liu, Xiaosong; Huang, Shijia; Duan, Tao; Du, Qiaoling (Frontiers in Endocrinology, 2021)
Objective To investigate the association between hypothyroxinaemia and the risk of preeclampsia-eclampsia and gestational hypertension. Design Historical cohort study. Methods The study included pregnant individuals who delivered singleton live-born and had at least one thyroid function assessment during pregnancy at a tertiary hospital. Hypothyroxinaemia was defined as thyroid-stimulating hormone (TSH) levels within the normal reference range and free thyroxine (FT4) levels lower than the tenth percentile. Risk ratios (RRs) with 95% confidence intervals (95% CIs) for preeclampsia-eclampsia and gestational hypertension between women with and without a history of hypothyroxinaemia during pregnancy were estimated using a generalized estimating equation model. Results A total of 59463 women with singleton live-born were included in the analysis. Logistic regression models with restricted cubic spline suggested that there was a U-shaped association between FT4 levels and preeclampsia-eclampsia risk. Compared with euthyroid women, those with hypothyroxinaemia had an increased risk of preeclampsia-eclampsia (RR=1.16, 95% CI: 1.02–1.31), and the risk increased with the increasing severity of hypothyroxinaemia (P for trend < 0.001). Moreover, persistent hypothyroxinaemia from the first to second trimesters was strongly associated with an increased risk of preeclampsia-eclampsia (RR=1.37, 95% CI: 1.03–1.83), especially for women with severe hypothyroxinaemia (RR=1.70, 95% CI: 1.12–2.58). In contrast, there was no association between hypothyroxinaemia and gestational hypertension. Conclusion Our study suggested that hypothyroxinaemia was only associated with an increased risk of preeclampsia-eclampsia, especially in women with persistent hypothyroxinaemia in the first half of pregnancy. Analyses of the associated risk of gestational hypertension with hypothyroxinaemia were not significant.